Impact of Innovative Anastomotic Techniques on Anastomotic Leak Rates and Clinical Outcomes Following Gastrectomy - Muhammad Amin, Irshad Ahmad, Ajmal Khan Bazai, Abdullah Jan, Usman Aslam, Jamshed Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To evaluate the impact of innovative anastomotic techniques on anastomotic leak rates and clinical outcomes following gastrectomy. Place and Duration of Study: Department of General Surgery, Northwest Teaching Hospital, Peshawar, from Oct 2022 to September 2023. Methodology: This randomized controlled trial included 100 patients undergoing gastrectomy for gastric cancer or benign conditions. Patients were randomly allocated into two groups: Group A (conventional anastomotic technique) and Group B (innovative anastomotic technique). The primary outcome was the rate of anastomotic leaks. Secondary outcomes included postoperative complications, surgery duration, and hospital stay. Data were analyzed using chi-square and t-tests, with a p-value of <0.05 considered significant. Results: Anastomotic leak rates were 10% in the conventional group and 4% in the innovative group (p=0.24). Postoperative complications occurred in 24% of patients in the conventional group and 16% in the innovative group (p=0.32). Surgery duration was significantly shorter in the innovative group (160 ± 20 minutes) compared to the conventional group (175 ± 25 minutes, p=0.03). Hospital stay was shorter in the innovative group (12 ± 2 days) compared to the conventional group (14 ± 3 days, p=0.05). Conclusion: Innovative anastomotic techniques demonstrated a trend toward reduced leak rates, shorter surgery duration, and hospital stay, although the difference in leak rates was not statistically significant. Further studies with larger sample sizes are recommended. Keywords: Gastrectomy, anastomotic leak, innovative techniques, postoperative complications, randomized controlled trial.